2022
DOI: 10.3389/fonc.2022.939021
|View full text |Cite
|
Sign up to set email alerts
|

Identified Gefitinib Metabolism-Related lncRNAs can be Applied to Predict Prognosis, Tumor Microenvironment, and Drug Sensitivity in Non-Small Cell Lung Cancer

Abstract: Gefitinib has shown promising efficacy in the treatment of patients with locally advanced or metastatic EGFR-mutated non-small cell lung cancer (NSCLC). Molecular biomarkers for gefitinib metabolism-related lncRNAs have not yet been elucidated. Here, we downloaded relevant genes and matched them to relevant lncRNAs. We then used univariate, LASSO, and multivariate regression to screen for significant genes to construct prognostic models. We investigated TME and drug sensitivity by risk score data. All lncRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…Yue, N. et al ( Yue et al, 2020 ) found that the high expression of lncRNA pSMG3-AS1 played a carcinogenic role in the development of LUAD. At the same time, recent studies have also shown that it is possible to predict the prognosis of cancer patients by exploring the potential relationship between coding genes and lncRNAs ( Wang et al, 2019b ; Ye et al, 2022 ). In this study, we were inspired by the mechanism by which both molecular chaperones and lncRNAs can be involved in the occurrence and development of LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Yue, N. et al ( Yue et al, 2020 ) found that the high expression of lncRNA pSMG3-AS1 played a carcinogenic role in the development of LUAD. At the same time, recent studies have also shown that it is possible to predict the prognosis of cancer patients by exploring the potential relationship between coding genes and lncRNAs ( Wang et al, 2019b ; Ye et al, 2022 ). In this study, we were inspired by the mechanism by which both molecular chaperones and lncRNAs can be involved in the occurrence and development of LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…The formula for the Cox proportional hazards model is as follows [ [14] , [15] , [16] ]: h (t, X) = h (t) exp (β X + β X + … + β X) …”
Section: Methodsmentioning
confidence: 99%
“…13 immune functions and corresponding gene sets studied by Ye et al were downloaded [ 20 ]. “limma”, “GSVA”, “GSEABase”, “Pheatmap” and “reshape2” packages of R software were used to analyze the co-expression between immune function gene sets and HGR/LGR in the training group, test group, and all patients to obtain the correlation of immune function in HRG and LRG.…”
Section: Methodsmentioning
confidence: 99%
“…Their findings revealed that lncRNA-ATB promoted lung cancer progression by inhibiting miR-200a expression and reversed the promotion of b-linked protein expression to promote apoptosis in NSCLC cells (116).The newly discovered lncRNA SET binding factor 2 antisense RNA 1 (LncRNA SBF2-AS1) is involved in the progression of many cancers like lung, breast, hepatocellular carcinoma, thyroid, gastric, colorectal cancers and others (118). Interestingly, Weilong Ye et al identified 13 lncRNAs related to Gefitinib metabolism and applied them to build the prognostic model of NSCLC patients (119). This proves that lncRNA studies are not limited to particular tumour tissue, and more and more studies have proposed new ideas for the diagnosis, treatment and prognosis of lncRNAs.…”
Section: Lncrnas Directly Regulate Lung Cancermentioning
confidence: 99%
“…Interestingly, Weilong Ye et al. identified 13 lncRNAs related to Gefitinib metabolism and applied them to build the prognostic model of NSCLC patients ( 119 ). This proves that lncRNA studies are not limited to particular tumour tissue, and more and more studies have proposed new ideas for the diagnosis, treatment and prognosis of lncRNAs.…”
Section: The Roles Of Lncrnas In Lung Cancermentioning
confidence: 99%